Estudo fitoquímico de hancornia speciosa: isolamento, atividade biológica e caracterização por cromatografia líquida de eficiência ultra elevada acoplada à espectrometria de massas - Bastos , Katherine Xavier (2016)
Apocynaceae is a botanical family that includes between 3700 and 5100 species are distributed almost worldwide, but mainly in tropical and subtropical regions. In Brazil there are about 90 genera and 850 species, inhabiting different vegetation types. Within this large botanical family is gender Hancornia, which is considered monotypic and therefore its unique species is Hancornia speciosa Gomes, and is abundant in the northeastern cerrado. In view of this, this paper aims to study fitoquimicamente Hancornia speciosa thus contributing to the expansion of the chemical knowledge of the species. In addition to evaluating the antifungal activity of the extract and isolated compounds. For the study, the plant material after drying and pulverizing, was subjected to extraction and chromatography processes for isolation of chemical constituents. Techniques such as Cromatrografia Liquid High efficiency and Ultra-high Performance Liquid Chromatography were employed at work. The chemical structure of the substances was determined by 1H Nuclear Magnetic Resonance, 13C and dimensional comparisons with literature data. Chromatographic fractionation of the chloroform phase resulted in the isolation of caffeate acetate, the ethyl acetate phase gave the isoquecetrina beyond the narigenina, and a mix of acid 4,5-O-E- caffeoyl-quinic acid with 3,5-di –O-E- caffeoyl-quinic the butanol phase. All these compounds were first reported in Hancornia speciosa. Characterization of the extract of Hancornia speciosa leaves by Ultra-high Performance Liquid Chromatography coupled to Mass Spectrometry also provided the identification of twenty-four compounds. Since the study of the antifungal activity of the extracts provide a positive result, but compounds isolated did not provide a positive result, not being able to inhibit the growth of the strains in any concentration tested. This work contributed indicating that this species is bioprodutora phenolic compounds, as demonstrated in this phytochemical study.